Living on a Poverty Income: The Role of Non-Governmental Agencies in the Scramble for Resources - Ronald Angel; Laura Lein (Washington University Journal of Law & Policy, 2006)
Our objective is to illustrate the precariousness of the formal social service safety net for low-income families and to argue that social inequality in urban America is exacerbated by the inequitable distribution of more formal sources of support. Ultimately, we examine whether the current system of service delivery for poor families is adequate, and what toll these fragmented and discontinuous services take on a family’s ability to thrive.
Keywords: Poverty; Nonprofit organizations; Nongovernmental organizations; Public welfare; Working poor; United States; Family services